Rancang Bangun Alat Keamanan pada Ruangan Menggunakan Arduino dan Sensor PIR Berbasis SMS Gateway - Teuku Muhammad Razi; Ipan Suandi; Muhammad Muhammad (Politeknik Negeri Lhokseumawe, 2022)
The design of security devices in the room using Arduino and PIR sensors based on SMS Gateway has been carried out to anticipate security problems in the room. The purpose of this study is to design and build a security system in a room with a PIR sensor based on SMS Gateway, where when someone tries to steal, if the homeowner is at work or is far from the scene, they can immediately go to the location. The system is designed so that it can be activated and deactivated remotely via SMS (Short Message Service). The test method used is to determine the sensitivity of the sensor in detecting objects both at the closest and furthest distances to objects in the room. The results of the tests carried out are measuring the voltage when the tool is used, the sensitivity distance of the sensor and SMS commands and the response time of sending SMS. From the test results, it is found that this security system is able to provide or send a danger signal via SMS wherever we are. The results of the voltage measurement obtained are 5 volts on the PIR sensor, microcontroller, and SIM800 module. The PIR sensor used can detect movement with a maximum distance of 600 cm. The average SMS response time was 8.93 seconds.